Nanostructured (Ti,Cu)N dry electrodes for advanced control of the neuromuscular activity - Lopes, Claudia; Veloso, Hugo; Hayes, Makenna; Cullinan, Michael; Vaz, Filipe (IEEE sensors journal, 2023)
This research reports a novel concept of dry surface electrodes designed to act in a dual-role biofeedback process: monitoring and stimulating the muscle's electrical activity. A new strategy based on 3D printed polymeric disk-shaped substrates functionalized with nanostructured (Ti,Cu)N thin films to be integrated into rehabilitation wearables. Five different chemical compositions with different microstructural features were grown by DC magnetron sputtering on polyurethane, polylactide, and cellulose polymers and tested as electrodes. In the first phase, the EMG activity for both resting and muscle contraction of the bicep muscle was assessed using the LabVIEW software coupled to a NI 9234 signal data acquisition system and processed with MATLAB algorithms. The second phase tested the maximum electrical stimulation capable of being delivered without crosstalking between stimulation and sensing processes, using a TENS 7000 commercial unit. The tests highlighted the potential of the flexible polyurethane bases among their counterparts. Whereas the dense and soft electrodes of titanium doped with 25.6.% of copper were able to stimulate at a 100 mA full current output without discomfort for the subject exhibiting simultaneously the lowest EMG detection limit. The research conducted enhances the strong potential of using dry electrodes in new technologies and strategies capable of delivering primary and integrated care adapted to foster functional abilities.